2013
DOI: 10.1371/journal.pone.0055475
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Knockdown Resistance, Metabolic Detoxification and Organismal Resistance to Pyrethroids in Anopheles sinensis

Abstract: Anopheles sinensis is the most important vector of malaria in Southeast Asia, including China. Currently, the most effective measure to prevent malaria transmission relies on vector control through the use of insecticides, primarily pyrethroids. Extensive use of insecticides poses strong selection pressure on mosquito populations for resistance. Resistance to insecticides can arise due to mutations in the insecticide target site (target site resistance), which in the case of pyrethroids is the para-type sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 63 publications
(114 citation statements)
references
References 48 publications
9
101
0
4
Order By: Relevance
“…Further, metabolic detoxification enzymes were found to be very important in An. sinensis [16]. The present study confirmed that transcripts with the largest increase in expression were in metabolic pathways, particularly those coding for glutathione S-transferase, P450 monooxygenase, and cytochrome C oxidase detoxification enzymes.…”
Section: Discussionsupporting
confidence: 83%
“…Further, metabolic detoxification enzymes were found to be very important in An. sinensis [16]. The present study confirmed that transcripts with the largest increase in expression were in metabolic pathways, particularly those coding for glutathione S-transferase, P450 monooxygenase, and cytochrome C oxidase detoxification enzymes.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, kdr allele frequency had no predictive power when the populations completely lacked kdr mutations, as in the An. sinensis populations in Yunnan province [30]. Similar phenomena were found in An.…”
Section: Discussionsupporting
confidence: 67%
“…Measurement of P450 and GST activity followed the methods of Penilla et al [40] and Zhong et al [30]. COE activity was measured following the method of Hosokawa and Satoh [41].…”
Section: Methodsmentioning
confidence: 99%
“…We followed our previously published protocol to measure monooxygenase and GST activities [23]. Mean absorbance values for each tested mosquito and enzyme were converted into enzyme activity and standardized based on the total protein amount.…”
Section: Methodsmentioning
confidence: 99%